2018
DOI: 10.1002/lt.25292
|View full text |Cite
|
Sign up to set email alerts
|

Primary Stent Placement for Hepatic Artery Stenosis After Liver Transplantation: Improving Primary Patency and Reintervention Rates

Abstract: Recent studies have reported high rates of reintervention after primary stenting for hepatic artery stenosis (HAS) due to the loss of primary patency. The aims of this study were to evaluate the outcomes of primary stenting after HAS in a large cohort with longterm follow-up. After institutional review board approval, all patients undergoing liver transplantation between 2003 and 2017 at a single institution were evaluated for occurrence of hepatic artery complications. HAS occurred in 37/454 (8%) of patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
0
14
1
Order By: Relevance
“…Another crucial matter is the role of non‐occlusive arterial flow reduction in the development of ITBL and graft loss. Non‐occlusive arterial complications can potentially lead to HAT development 2,3,25 . Our study demonstrated that prompt identification and restoration of adequate arterial supply in HAS/SASS cases allow to salvage the grafts and avoid sepsis compared with HAT cases.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…Another crucial matter is the role of non‐occlusive arterial flow reduction in the development of ITBL and graft loss. Non‐occlusive arterial complications can potentially lead to HAT development 2,3,25 . Our study demonstrated that prompt identification and restoration of adequate arterial supply in HAS/SASS cases allow to salvage the grafts and avoid sepsis compared with HAT cases.…”
Section: Discussionmentioning
confidence: 66%
“…Nonocclusive arterial complications can potentially lead to HAT development. 2,3,25 Our study demonstrated that prompt identi- HAT is still a formidable complication and is characterized by high graft loss and ITBL rates. Assumptions about the role of arterial ischemia time have been suggested earlier.…”
Section: Ta B L Ementioning
confidence: 68%
See 3 more Smart Citations